Prevalence of hepatitis B infection and its associated factors among pregnant mothers attending antenatal care at public hospitals at Hararghe, Eastern Ethiopia - Umer, Abbas; Teklemariam, Zelalem; Ayele, Firayad; Mengesha, Melkamu Merid (Frontiers in Global Women's Health, 2023)
Background Hepatitis B infection is one of the world's most serious public health problems, causing significant morbidity and mortality. More than 2 billion individuals around the world have been infected with the hepatitis B virus (HBV), and approximately 400 million people are chronically infected with the virus, with more than a million dying each year from hepatitis B virus-related liver disease. A newborn infant whose mother is positive for both HBsAg and HBeAg has a 90% chance of developing chronic infection by the age of 6. Its infectivity is a 100 times that of the human immunodeficiency virus, but it receives little attention in public health. Therefore, this study was conducted to assess the prevalence of hepatitis B infection and its associated factors among pregnant mothers attending antenatal care at public hospitals in west Hararghe, eastern Ethiopia 2020. Method This institution-based cross-sectional study was conducted on 300 pregnant mothers selected by systematic random sampling from September to December 2020. Data were collected by face-to-face interview using a pretested structured questionnaire. A blood sample was collected and tested for hepatitis B surface antigen using the enzyme-linked immunosorbent assay test method. Data were entered into EpiData version 3.1 and exported to Statistical Package for the Social Science version 22 for analysis. Bivariate and multivariable logistic regressions were used to assess the association between outcome and predictor variables. P-value <0.05 was considered to be statistically significant. Results The overall seroprevalence of hepatitis B virus infection was 8% [95% confidence interval (CI): 5.3–11.0] among pregnant mothers. History of tonsillectomy [adjusted odd ratio (AOR) = 5.7; 95% CI: 1.3–23.9], tattoo (AOR = 4.3; 95% CI: 1.1, 17.0), having multiple sexual partners (AOR = 10.8; 95% CI: 2.5, 45.9), and history of contact with jaundiced patients (AOR = 5.6; 95% CI: 1.2, 25.7) were factors associated with the seroprevalence of hepatitis B virus infection among pregnant mothers. Conclusion The hepatitis B virus was highly prevalent. A history of tonsillectomy, tattooing, having multiple partners, and contact with jaundiced patients were factors associated with hepatitis B virus infection. To reduce HBV transmissions, the government should increase HBV vaccination coverage. All newborns should receive the hepatitis B vaccine as soon as possible after birth. It is also recommended that all pregnant women have HBsAg testing and antiviral prophylaxis to reduce the risk of transmission from mother to child. Hospitals, districts, regional health bureaus, and medical professionals should also educate pregnant women about hepatitis B virus transmission and prevention, both in the hospital and in the community, with a focus on modifiable risk factors.